On multidimensional local limit theorem - Raudeliūnas, A. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. К. Рауделюнас. О многомерной локальной предельной теореме A. Raudeliūnas. Daugiamatės lokalinės ribinės teoremos klausimu